Improvement of Manufacturing Operations through a Lean Management Approach: A Case Study in the Pharmaceutical Industry. (6th November 2014) - Nenni, Maria Elena; Giustiniano, Luca; Pirolo, Luca
This paper aims to demonstrate the positive effect of a Lean Management (LM) approach to increasing efficiency, even in a company which is subject to critical market issues. The pharmaceutical industry is a well-known example of a crisis-affected context and companies have directed attention to Lean Management for a long time, but they are stable in increasing effectiveness. This research uses a case study to move the attention to efficiency as an attractive LM goal. The result of this study provides a reference for academia as well as the business field.